Absence of genetic linkage of chromosome 5q31 with asthma and atopy in the general population - Kamitani, A; Wong, Z Y; Dickson, P; van Herwerden, L; Raven, J; Forbes, A B; Abramson, M J; Walters, E H; Harrap, S B (Thorax, 1997)
BACKGROUND: Clinical asthma is associated with increased serum total immunoglobulin E (IgE), atopy (skin prick test positivity to common aeroallergens), and bronchial hyperreactivity (BHR) to non-specific stimuli (positive methacholine challenge test). A region on chromosome 5q31-33 has been linked with increased total serum IgE and BHR. A study of the genetic linkage of this region with clinical asthma and atopy was therefore undertaken. METHODS: A polymorphic microsatellite marker in chromosome 5q31 (D5S399) was studied in 119 sibling pairs recruited from the general population who shared asthma, atopy, and/or BHR. Based on our population distribution of 13 different alleles, it was expected that by chance alone sibling pairs would share on average 1.24 alleles and that a significant excess would indicate genetic linkage. RESULTS: No evidence of linkage was found in 45 siblings concordant for asthma (shared alleles = 1.09, p = 0.95), in 103 sibling pairs with atopy (shared alleles = 1.18, p = 0.82), in 51 sibling pairs with BHR (shared alleles = 1.22, p = 0.62), or in 68 sibling pairs who shared atopy in the absence of BHR (shared alleles = 1.22, p = 0.61). A slight non-significant excess of shared alleles (1.44, p = 0.11) was observed in siblings who shared BHR without atopy. CONCLUSIONS: No evidence of genetic linkage of chromosome 5q31 with either clinical asthma or atopy was therefore detected in the population studied. Linkage between chromosome 5q and BHR needs further investigation.